Behaviour and design of cold-formed steel built-up section beams with different screw arrangements. (October 2018) - Wang, Liping; Young, Ben
Abstract: An experimental and numerical investigation of cold-formed steel built-up beams with different screw arrangements is presented in this paper. A total of 35 beams were tested under four-point bending with different screw arrangements in the moment span. The built-up sections were assembled using self-tapping screws from either two lipped channels connected back-to-back at the web to form an open section or two plain channels connected face-to-face at the flanges to form a closed section. Finite element (FE) models have been developed and validated against the test results for the built-up open section beams and built-up closed section beams, respectively. It is shown that the FE models can accurately predict the behaviour of cold-formed steel built-up beams with different screw arrangements. A parametric study on built-up beams with larger span and various screw spacing was further carried out using the verified FE models. The test and numerical results were compared with the design strengths predicted by the direct strength method (DSM) for cold-formed steel structures, with contingent considerations of the screws when determining the elastic buckling moments in the finite strip analysis. A reliability analysis was performed to evaluate the reliability of the current DSM equations. It is shown that the current DSM equations can predict the design strengths of built-up open section beams well in this study, with the assumption that the strength of the built-up section is the sum of two component profiles. However, the design equations for local buckling strength are generally conservative for the built-up closed section beams failed by local buckling. Meanwhile, the design equations for lateral-torsional buckling (LTB) strength cannot be directly used for the built-up closed section beams with relatively large screw spacing that failed by LTB with cross section distortion or separation of two component channels. It should be noted that LTB mode with cross section distortion was found in built-up closed section beams with large screw spacing. A modified design rule based on DSM is then proposed, which is shown to improve the accuracy of the predicted strengths. Moreover, the maximum longitudinal screw spacing for built-up closed section beams was also recommended for design practice. Highlights: Beam tests on cold-formed steel built-up sections with different screw arrangements were conducted. FE models of built-up open and closed section beams were developed and verified with test results. Parametric study on different sections with a wide range of screw spacing was performed. Current direct strength method is assessed by comparing with test and numerical data. Design rule for cold-formed steel built-up closed section beams considering screw spacing is recommended.